Research on additional damping control strategy of flexible distribution transformer - Guo, Guowei; Wang, Jinfeng; Zhan, Ximei; Liu, Zhu; Gong, Dehuang; Tang, Aihong; Shang, Yufei; Wang, Zihan (Frontiers in Energy Research, 2024)
Disturbances to the power system may lead to relative swing between synchronous generator rotors, causing low-frequency oscillation problems in the absence of damping. In this article, based on the single-machine infinity system containing flexible distribution transformer and synchronous generator, the linearized state equations of the system is deduced by the small-signal modeling. The mechanism of flexible distribution transformer on the rotor speed of synchronous generator is analyzed. The influence factors of flexible distribution transformer on the rotor speed of synchronous generator are analyzed.The equation of the additional damping provided by the flexible distribution transformer to this system is constructed. It was concluded that by controlling the output voltage of the regulating converter in the flexible distribution transformer, the rotor speed of the synchronous generator can be varied to increase the system damping. An additional damping control strategy for flexible distribution transformer is proposed. The simulation verifies that the proposed control strategy can effectively suppress the oscillation amplitude of each electrical quantity and shorten the oscillation duration when the system is subjected to large and small perturbations.